If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3x + (3x + 4) = 101 Reorder the terms: X + 3x + (4 + 3x) = 101 Remove parenthesis around (4 + 3x) X + 3x + 4 + 3x = 101 Reorder the terms: 4 + X + 3x + 3x = 101 Combine like terms: 3x + 3x = 6x 4 + X + 6x = 101 Solving 4 + X + 6x = 101 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + X + -4 + 6x = 101 + -4 Reorder the terms: 4 + -4 + X + 6x = 101 + -4 Combine like terms: 4 + -4 = 0 0 + X + 6x = 101 + -4 X + 6x = 101 + -4 Combine like terms: 101 + -4 = 97 X + 6x = 97 Add '-6x' to each side of the equation. X + 6x + -6x = 97 + -6x Combine like terms: 6x + -6x = 0 X + 0 = 97 + -6x X = 97 + -6x Simplifying X = 97 + -6x
| 48+3a=a | | 3x^5-2x^3+7=0 | | -9=-9y+18 | | -10.6-7y=14 | | x+3/2+4/3=x+17/6-x/2 | | 2(b+2)+b=2(6+b)+1 | | a-2a+3a=12 | | 2y+7x=95 | | 2x+y=8y | | 4(c+5)=-1(c+20) | | (9+2x)3=4+13x | | -3x-4+7x-2=4x-3+7x-4 | | -4(8+4n)=40-7n | | 2(q+2)=q+1 | | 3x-14=-8x-36 | | 5+5r-2=9r+11-3r | | log(4)+log(x-1)=log(3x) | | 3x+2y-4x+3= | | (9+7i)(8-3i)= | | 8z+5=1 | | 2y+5x=77 | | 4x+7-x=13 | | -7x-10=-136 | | 12x-3x^2=12 | | 9(t-3)+3t=6(2t+4)-12 | | a+2a+3a=12 | | -12(x-1)=4(x+9) | | 4x^2-16x-208=0 | | 8x+4y+6u+2z=-16 | | x^3-x^2-3x-1=0 | | 29-11=30-x | | 95-63=x-60 |